Town in the New World During the Spanish Colonization of the Americas - A. F. Kofman (Ибероамериканские тетради)
Spanish conquistadors drew a clear distinction between their objectives as they embarked on expeditions, with two contrasting verbs highlighting the difference: the verb poblar (to populate) involved establishing settlements and towns (pueblos), whereas the verb rescatar implied trading or even raiding the land. Founding a town meant the conquistadors started to colonize the area, relying on it as a «door» to go «deep in to the territory». Spanish colonization of the New World was marked by an important feature: any settlement was granted the status of a town and center from the outset. Any fort served as a town, a foothold for settlement in a vast unexplored area; it was the antithesis of endless and chaotic wilderness. The image of an indigenous town that conquistadors had in mind manifested itself in two forms, namely, a real town and a mythical one. While the perception of Spanish towns in the New World was unfailingly positive, an indigenous town, whether a real or mythical one, was deemed ambivalent, dangerous yet appealing.Mythical indigenous towns played a more important role in the history of Spanish exploration and conquest of the New World than real indigenous towns. It was the quest for mythical kingdoms and towns that became the main driving force behind Spanish colonization of the New World, as most major expeditions in America were launched to pursue pipe dreams. Those expeditions failed to generate wealth yet they resulted in geographical discoveries. Conquistadors’ fantasies prompted them to explore the great wilderness in a short period of time from a historical perspective.